A devil went down to Georgia : race, power, privilege, and the murder of Lita McClinton - Landau, Deb Miller (Pegasus Books, 2024)
Describes the 1987 murder of Lita McClinton Sullivan, a Black, Atlanta socialite in a suburb outside Atlanta in broad daylight by a for-hire, ex-con killer enlisted by Jim Sullivan, her estranged, white husband who saw her as the cause of his financial troubles.